2003
DOI: 10.1007/s00253-003-1254-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient 40�C fermentation of l-lysine by a new Corynebacterium glutamicum mutant developed by genome breeding

Abstract: We have recently developed a new L-lysine-producing mutant of Corynebacterium glutamicum by "genome breeding" consisting of characterization and reconstitution of a mutation set essential for high-level production. The strain AHP-3 was examined for L-lysine fermentation on glucose at temperatures above 35 degrees C, at which no examples of efficient L-lysine production have been reported for this organism. We found that the strain had inherited the thermotolerance that the original coryneform bacteria was endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…A second is improved stress-tolerance, which has allowed fermentation at higher temperatures than is traditionally practiced. The new strain showed efficient L-lysine production at 40ºC, whereas classical strains could not function above 35ºC [14]. This feature not only allows reduction of cooling costs, but also enables cost-effective manufacture in tropical regions that have easy access to low-cost carbon sources such as molasses and tapioca.…”
Section: Verifying the Performance Of The Minimally Mutated Strainmentioning
confidence: 94%
See 1 more Smart Citation
“…A second is improved stress-tolerance, which has allowed fermentation at higher temperatures than is traditionally practiced. The new strain showed efficient L-lysine production at 40ºC, whereas classical strains could not function above 35ºC [14]. This feature not only allows reduction of cooling costs, but also enables cost-effective manufacture in tropical regions that have easy access to low-cost carbon sources such as molasses and tapioca.…”
Section: Verifying the Performance Of The Minimally Mutated Strainmentioning
confidence: 94%
“…Reconstructing an L-lysine producer according to genome information Reconstruction of an L-lysine producer is carried out in the following way [8,9,[14][15][16].…”
mentioning
confidence: 99%
“…The L-lysine production by the six isogenic mutants were investigated using 5-liter jar fermentors both under traditional 30 C conditions and, in addition, under suboptimal 40 C conditions which could allow reduction of cooling costs in industrial processes. 23,24) Figure 1 shows the profiles obtained in fed-batch fermentor cultivation with LPG1 medium 19,20) to which glucose was added at an initial concentration of 5%, with a subsequent increase to 25%. The six lysC mutants all produced large amounts of L-lysine at both temperatures, but it was found that final titers and productivities were significantly different among the six isogenic mutants at either temperature (Table 2).…”
Section: )mentioning
confidence: 99%
“…To date, numerous mutants that can produce amino acids at high efficiency have been created. The worldwide demand for amino acids such as L-glutamate, L-lysine and L-threonine for use as animal feed and food additives has continued to increase (Hermann, 2003;Ohnishi et al, 2003). Therefore, it is desirable to develop C. glutamicum strains with improved productivity.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to developing strains of higher productivity using genome information has been reported (Ohnishi et al, 2003). But it does not yet deviate from the range of a single gene manipulation, and there still remain many unknown functions of genes in C. glutamicum.…”
Section: Introductionmentioning
confidence: 99%